The Presence of Flavonoids in Some Products and Fruits of the Genus Eugenia: An Integrative Review - Nogueira, Laiza Andrade; Figueiredo, Yuri Gomes; Ramos, Ana Luiza Coeli Cruz; Correia, Vinícius Tadeu da Veiga; Nunes, Bruna Vieira; Ribeiro, Lucas Victor; Franco, Ariele Oliveira; Ferreira, Ricardo Boavida; Sousa, Isabel; Mota, Joana; Batista-Santos, Paula; Araújo, Raquel Linhares Belo de; et al. (Frontiers in Food Science and Technology, 2022)
The Myrtaceae family, one of the most prominent botanical families, is represented in Brazil with different fruit species, rich in bioactive compounds and gastronomically appreciated. This study aimed to carry out an integrative review on the genus Eugenia, highlighting the pitangueira (E. uniflora L.), cagaiteira (E. dysenterica), grumixameira (E. brasiliensis), pereira (E. klotzschiana O. Berg), and uvaieira (E. pyriformis Cambess) and which flavonoids are present in these fruits. Articles published between 2016 and 2021 were selected from the following databases: Google Scholar, Periódicos CAPES, Scielo, and Science Direct. According to each database, the descriptors used as a search strategy addressed the popular and scientific names of the five selected species, associated or not with the term “flavonoid,” according to each database. The results showed that quercetin was the main flavonoid identified in the fruits, and the principal extraction method used was HPLC. Other interesting compounds, such as catechin, epicatechin, rutin, myricetin, and kaempferol, were also found. However, the amount and type of flavonoids detected varied according to the applied methodology. Hence, these studies highlight the importance of species of the genus Eugenia, which promotes beneficial health effects and possible applicability to the food and pharmaceutical industry.